Effect of the Diffusion of Copper Atoms in Polycrystalline CdTe Films Doped with Pb Atoms - Utamuradova, Sharifa B.; Daliev, Shakhrukh Kh.; Muzafarova, Sultanpasha A.; Fayzullaev, Kakhramon M. (East European Journal of Physics, 2023)
The process of diffusion of labeled copper atoms in p-CdTe<Pb> coarse-block films with a columnar grain structure has been studied. The CdTe<Pb> film is a p-type semiconductor, where an increase in the Pb concentration in the composition of the CdTe films increases the resistivity ρ of the structure. When the Pb concentration in CdTe changes from 1018 to 5·1019 cm-3, the hole concentration decreases by more than 3 orders of magnitude at a constant operating level depth of EV + (0.4 ± 0.02) eV. This may indicate that the concentration of acceptor defects, which are formed in the films due to self-compensation upon doping with a PbCd donor, exceeds the number of the latter. Electrical measurements by the Hall method were carried out at a direct current and a temperature of 300 K. As a result, an increase in the temperature of films on a Mo-p-CdTe<Pb> substrate during annealing affects the electrical parameter of charge carrier mobility µ, it decreases significantly. X-ray diffraction analysis showed that on the diffraction patterns of samples of p-CdTe<Pb> films, all available reflections correspond to the CdTe phase and up to х = 0.08 do not contain reflections of impurity phases and have a cubic modification. Based on the results of the calculation, it was established that the low values of the diffusion coefficient of Cu atoms are due to the formation of associates of the A type , which are directly dependent on the concentration of atoms. Diffusion length Ln and lifetime τn of minority current carriers in large-block p-type cadmium telluride films, which can also be controlled by introducing lead atoms into cadmium telluride.